If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 48 = 4x + 12 Reorder the terms: 48 = 12 + 4x Solving 48 = 12 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 48 + -4x = 12 + 4x + -4x Combine like terms: 4x + -4x = 0 48 + -4x = 12 + 0 48 + -4x = 12 Add '-48' to each side of the equation. 48 + -48 + -4x = 12 + -48 Combine like terms: 48 + -48 = 0 0 + -4x = 12 + -48 -4x = 12 + -48 Combine like terms: 12 + -48 = -36 -4x = -36 Divide each side by '-4'. x = 9 Simplifying x = 9
| 12m=-58+118 | | -20=2(u+5)-7u | | 24+3x=18 | | 13m=-64+129 | | R+5r-5r+R=18 | | 2x+7x^2=0 | | 26-9x=108 | | 1c+8p=35 | | 72-4x=12 | | (-7x-6)(x-5)+(8x-9)(5-x)= | | X+2=30-15 | | 2x-8x+1=9+10x | | 12+3a-5-8=2a+3 | | 3÷7/6 | | (-7x-6)(x-5)+(8x-9)= | | 17x/3=24 | | 14.95+13x=-15.00+.39x | | f/5-2=4 | | 5x-7x+6=12(x-3) | | 15=6-9n | | 5-3a=5(ya+2)-5 | | 7m+32=12-n | | 0=3x^2-75 | | 2y=6+a | | 19p-11p-7p=19 | | 3p-4=5p+2 | | -4x-6x=18 | | (x+3)*2=10 | | X+X-X=12 | | 2(x+25)=75 | | 5y+4=20y-22 | | 5-2x=-5x+17 |